Risk factors for low bone mineral density in postmenopausal women with systemic sclerosis - A. O. Efremova; N. V. Toroptsova; O. V. Dobrovolskaya; M. N. Starovoitova; O. V. Desinova; O. A. Nikitinskaya (Научно-практическая ревматология, 2021)
Aim of the research – to determine the frequency of osteoporosis (OP) and to identify risk factors for a decrease in bone mineral density (BMD) in postmenopausal women with systemic sclerosis (SSс).Subjects and methods. The study included 113 postmenopausal women (median age – 60.0 [54.0; 63.0] years) with a reliable diagnosis of SSc according to the ACR/EULAR criteria (2013). The exclusion criterion was the presence of overlap syndromes. All women were interviewed according to a unified questionnaire, a laboratory and instrumental examination was conducted, including Dual-energy X-ray absorptiometry.Results. OP and osteopenia in at least one measurement area were diagnosed in 45.1% and 48.7% of women, respectively. Multivariate linear regression analysis revealed a negative effect of the total experience of taking glucocorticoids (GCs) on the value of BMD in the lumbar spine (b=–0.005; R2=0.136; p=0.017). Body mass index (BMI) (b=0.007; R2=0.208; p<0.001), glomerular filtration rate (GFR) (b=0.313; R2=0.213; p<0.001) is positive, and the cumulative dose of GCs (b=–0.269; R2=0.134; p<0.001), the duration of taking proton pump inhibitors (PPI) (b=–0.277; R2=0.291; p<0.001) and the duration of postmenopause (b=–0,223; R2=0.134; p<0.001) negatively affected the BMD of the femoral neck. BMD in the total hip (TH) was generally positively associated with BMI (b=0.493; R2=0.244; p<0.001), GFR (b=0.313; R2=0.150; p<0.001), 25-hydroxy calciferol level (b=0.273; R2=0.284; p=0.001), and negatively – with the cumulative dose of GCs (b=–0.219; R2=0.289; p<0.001).Conclusion. 93.8% of postmenopausal women with SSс had reduced BMD. Of the traditional risk factors, only BMI, the duration of postmenopause and the level of vitamin D had an impact on the state of BMD, and among the specific ones – the cumulative dose and duration of taking GCs, PPI and GFR.